2008
DOI: 10.1016/j.exphem.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The novel HSP90 inhibitor STA-9090 exhibits activity against Kit-dependent and -independent malignant mast cell tumors

Abstract: Objective Mutations of the receptor tyrosine kinase Kit occur in several human and canine cancers. While Kit inhibitors have activity in the clinical setting, they possess variable efficacy against particular forms of mutant Kit and drug resistance often develops over time. Inhibitors of heat shock protein 90 (HSP90), a chaperone for which Kit is a client protein, have demonstrated activity against human cancers and evidence suggests they downregulate several mutated and imatinib-resistant forms of Kit. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 48 publications
(64 reference statements)
3
88
0
2
Order By: Relevance
“…Canine MCTs with activating mutations in exon 11 respond well to TKIs that are now readily available for dogs. 42,47,61,69,111 Furthermore, high-grade MCTs lacking mutations or aberrant KIT expression have been reported to respond better to a chemotherapy protocol composed of vinblastine and prednisone than to TKI. 140 Similar to the results in dogs, cats with MCTs harboring a mutation in exon 8 have also been reported to have a favorable response to TKIs.…”
Section: Detection Of C-kit Mutations For Prognosis and Therapeutic Dmentioning
confidence: 99%
“…Canine MCTs with activating mutations in exon 11 respond well to TKIs that are now readily available for dogs. 42,47,61,69,111 Furthermore, high-grade MCTs lacking mutations or aberrant KIT expression have been reported to respond better to a chemotherapy protocol composed of vinblastine and prednisone than to TKI. 140 Similar to the results in dogs, cats with MCTs harboring a mutation in exon 8 have also been reported to have a favorable response to TKIs.…”
Section: Detection Of C-kit Mutations For Prognosis and Therapeutic Dmentioning
confidence: 99%
“…Antitumor efficacy ranges from minimal effects to tumor growth stasis but rarely tumor regression (9,14,15,(18)(19)(20). The variance in response between xenograft models may be attributable to differences in client protein dependence on Hsp90, tumor dependence on the client protein, kinetics of client protein degradation, and resynthesis, as well as, drug pharmacokinetic and pharmacologic properties.…”
Section: Introductionmentioning
confidence: 99%
“…20,29,38 Mutations result in constitutive activation of KIT, initiating signaling cascades leading to proliferation, survival, and invasion. 9,[15][16][17][18]21,22,29 One group reported that the presence of ITD mutations of c-KIT or aberrant cytoplasmic KIT protein localization was significantly associated with higher values of Ki67. 37 It is not clear from any study of cutaneous MCT if subcutaneous MCT were included; if so, the data could be compromised.…”
mentioning
confidence: 99%
“…6,9,11,[14][15][16][17][18][19][20][21][22]29,[36][37][38] Studies show that up to 30% of dogs with MCT have mutations in the juxtamembrane domain, 6,9,20,22,29,37,38 the majority of which are internal tandem duplications (ITD) in exon 11. The presence of these mutations is associated with higher-grade tumors.…”
mentioning
confidence: 99%